PENERAPAN TEKNOLOGI PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA DENGAN MAGGOT PADA PROGRAM KAMPUNG IKLIM DI KOTA BUKITTINGGI - Rudi Febriamansyah; Fuji Astuti Febria; Yulistriani Yulistriani; Defri Rahman; Resti Rahayu; Mahdi Mahdi (Jurnal Hilirisasi IPTEKS, 2021)
This activity is motivated by concern for the facts of climate change occurring globally and regionally. In response to this, the Indonesian government has also taken a number of concrete steps in all aspects of climate change adaptation and mitigation, both at the local, regional, and national levels. One national program that directly touches local communities is the climate village program known as "PROKLIM." The city of Bukittinggi has responded actively to this national program and has received national awards for the achievements of its activities in two community groups. The purpose of community service activities in the Climate Village Program is to increase the group's capacity in processing household organic waste through the application of Maggot cultivation from black soldier fly (BSF). The main methods of implementing the activities are training, providing assistance and companiment the target group. The activity results showed that the target group had the knowledge and skills to cultivate BSF and produce larvae/maggots. The target group had been able to produce fish/livestock feed from the larvae and developed plans to use the business results for the commercial market. One thing that becomes the next challenge is how to build continuity of feed availability for the maggot caterpillars, especially from household organic food leftovers in the group members' environment. In conclusion, the application of organic waste processing technology with maggot caterpillar cultivation is very potential to overcome the problem of waste in their neighborhood so that it can then be applied more widely in the city of Bukittinggi, to be able to overcome the problem of urban organic waste.